Postbiotics in pediatric clinical practice: position paper from Special Group of Latin American Society of Pediatric Gastroenterology, Hepatology and Nutrition (LASPGHAN) - Vázquez-Frias, Rodrigo; Vinderola, Gabriel; Abreu y Abreu, Ana Teresa; Angulo, Diana; Giler-Párraga, Natasha; Ladino, Liliana; Ortiz, Carolina; Pereira, Sebastián; Bustamante, Juan Pablo (Frontiers in Nutrition, 2025)
Postbiotics, defined by the ISAPP as preparations of inanimate microorganisms and/or their components that confer health benefits, represent a promising category of microbiome-derived solutions. This position paper highlights their clinical relevance, particularly in pediatrics, while addressing key aspects of definition, safety, quality, and strain-level specificity. Evidence supports the use of Lactobacillus LB –including L. fermentum CNCM I-2998 and L. delbrueckii subsp. lactis CNCM I-4831– in reducing the duration and severity of acute diarrhea in children. Other strains, such as Bifidobacterium breve C50, Streptococcus thermophilus 065, Lacticaseibacillus paracasei CBA L74, Lactiplantibacillus plantarum LPL28, and Ligilactobacillus salivarius AP-32, show promise in preventing infections, supporting oral health, and modulating immune responses. Additional postbiotics, including Limosilactobacillus reuteri DSM 17648, expand their potential into metabolic and gastrointestinal disorders. Collectively, postbiotics emerge as clinically valuable interventions, bridging science and medical practice.